Optimal Reconfiguration of Radial Distribution Networks Using PSO-CRO Approach for Loss Minimization and Voltage Stability Enhancement under Voltage Dependent Loads - Yadav L.K.; Barnwal A.K.; Verma M.K. (My University, 2025)
This paper manifests the static Voltage Stability Assessment (VSA), voltage deviation measurement, and loss reduction determination of voltage-dependent load model-based Radial Distribution System (RDS). The performance parameters for voltage stability assessment are calculated by the load flow method. A hybrid Particle Swarm Optimization-Coral Reef Optimization (PSO-CRO) approach is proposed for optimal network reconfiguration that significantly enhances voltage stability margin and reduces power loss in addition with voltage deviations at buses from desired values not only under Constant Power (CP) load but under a variety of voltage-dependent loads. Simulations are performed on IEEE 33-bus RDS for the unreconfigured case as well as optimally reconfigured case through a PSO-CRO based approach. A comparative study of simulation results obtained for both cases establishes the efficacy of PSO-CRO based network reconfiguration and the importance of consideration of voltage-dependent loads. © 2023 IEEE.